2003
DOI: 10.1557/jmr.2003.0362
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of tapered, conical-shaped titania nanotubes

Abstract: Using anodic oxidation with a time-dependent linearly varying anodization voltage, we have made films of tapered, conical-shaped titania nanotubes. The tapered, conical-shaped nanotubes were obtained by anodizing titanium foil in a 0.5% hydrofluoric acid electrolyte, with the anodization voltage linearly increased from 10-23 V at rates varying from 2.0-0.43 V/min. The linearly increasing anodization voltage results in a linearly increasing nanotube diameter, with the outcome being an array of conical-shaped na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
325
3
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(357 citation statements)
references
References 36 publications
8
325
3
5
Order By: Relevance
“…Moreover, DRS were also obtained in 200-800 nm wavelength range to calculate the band gap energy of the samples. It is known that the applied voltage is one of the most important parameters on nanotubes morphology and by increasing the anodizing voltage, tubes diameters can be increased due to the improved chemical etching through the more florid ion arrived to the Ti substrate [28]. The TiO 2 nanotubes diameters and wall thickness depend on anodizing voltage as follows [38]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, DRS were also obtained in 200-800 nm wavelength range to calculate the band gap energy of the samples. It is known that the applied voltage is one of the most important parameters on nanotubes morphology and by increasing the anodizing voltage, tubes diameters can be increased due to the improved chemical etching through the more florid ion arrived to the Ti substrate [28]. The TiO 2 nanotubes diameters and wall thickness depend on anodizing voltage as follows [38]:…”
Section: Methodsmentioning
confidence: 99%
“…Different approaches were suggested so far to improve dye cells efficiency like replacing TiO 2 nanoparticles with nanotubes since one dimensional TiO 2 nanotube arrays provide direct path for electrons and improves the electron transport velocity and also cause reduction of the charge recombination [18,19]. TiO 2 nanotubes have been prepared by various methods such as sol-gel [20][21][22], liquid-phase deposition [23], hydrothermal [24][25][26] and electrochemical anodization processes [27,28]. Amongst them, the electrochemical anodization of Titanium foil is producing compacted and oriented arrays and is known to be one of the most simple and low cost processes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Grimes and coworkers [15] reported an effective route in 2001 toward the fabrication of titania nanotube arrays by anodization of a titanium foil in fluoride-based electrolyte solutions by using fluoride ions as effective etchants. It has been found that the nanotube morphology [22], length and pore size [23], as well as wall thickness [24] might be readily controlled by varied experimental parameters such as electrolyte composition, solution pH, as well as electrode voltage [25].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were anodized in a hydrofluoric acid (HF) solution at room temperature with magnetic stirring. According to previous studies conducted by Gong et al [13,14], the direct-current voltage was set to 20 V and the distance between platinum cathode and anode was kept at about 1 cm during anodization. One set of titanium samples was anodized in 1.5 wt% HF for 5 min to produce a particulate structure while the other set was anodized in 0.5 wt% HF for 20 min resulting in a tube-like structure.…”
Section: Anodization Of Titanium Substratesmentioning
confidence: 99%
“…However, few studies have been conducted examining the effects of nanoroughness on cell function in the absence of changes in chemistry. Following the work by Gong et al [13,14], anodization techniques used in the present study enabled the fabrication of titanium oxide films with unique nanoarchitectures by using hydrofluoric acid (HF) as the electrolyte. The objective of this in vitro study is to synthesize nano-rough surfaces on titanium through anodization and determine osteoblast adhesion on such novel surfaces compared to conventional ones.…”
Section: Introductionmentioning
confidence: 99%